Female behavioral strategies during consortship in Tibetan macaques (Macaca thibetana). Issue 14 (22nd June 2021) - Zhang, Qi‐Xin; Sun, Lixing; Xia, Dong‐Po; Li, Jin‐Hua
Abstract: Consortship has been defined as a temporary association between an adult male and an estrous/receptive female. It has been considered as male mating strategies to improve male mating success and potential reproductive success. However, the female roles have been more or less neglected, and thus, less is known about female behavioral strategies during the consortship periods. In this study, during the two consecutive mating seasons, we collected behavioral data of free‐ranging Tibetan macaques ( Macaca thibetana ) habituated in Mt. Huangshan, China, to investigate female behaviors when she was consorted by an adult male. The results showed that (a) females were more likely to approach and exhibit sexual solicitation to their consorting males during the consorted period, and females also exhibited less approach to their nonconsorting males; (b) females exhibited strong responses (either departed distantly or formed affiliative relationships with their consorting male partner) when their consorting males mated with rival females or showed sexual motivation toward rival females; (c) female preferences were positively correlated to the duration of consortships and the frequencies of ejaculation copulations, independent of the social ranks of their consorting male partners. Our results suggested that female strategies played much more important roles in forming and maintaining consortship than previously assumed. It provides new insight into understanding female adaptive strategies to male strategies by forming consortships in multimale–multifemale primate species when males could not identify female's fertile phase accurately. Abstract : The study is relevant in today's society and should be of interest to a wide readership. The contribution of the study and the wider implications of the results are clearly presented and discussed in the manuscript.